The Iran job [videorecording (DVD)] - Schauder, Till; Schauder, Till (Film Movement series., 2014)
At the height of international tension between America and Iran, Kevin Sheppard, an African-American basketball player accepts an offer to play professional basketball in Iran. What begins as a desire to "explore the unknown" ends in an emotional roller-coaster as he forms an unlikely alliance with three young Iranian women against the backdrop of revolutionary social upheaval in Iran.